2015
DOI: 10.1515/aep-2015-0041
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and risk assessment of heavy metals in bottom sediments of two small dam reservoirs (south-east Poland)

Abstract: Sediments of two dam reservoirs in SE Poland, Zalew Zemborzycki (ZZ) and Brody Iłżeckie (BI) were studied. The sediments from both reservoirs were sampled in the transects perpendicular to the shoreline, at the river inflow and the frontal dam. The total concentration of Mn, Zn, Pb, Cd, Cu, Cr and Ni was determined by ICP-EAS method after the sample digestion in the mixture of concentrated HNO3 and HClO4 acids. The statistical analyses: value intervals, mean values, variation coefficient, the median and the sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 27 publications
(32 reference statements)
0
18
0
1
Order By: Relevance
“…Many indices have been developed to evaluate the environmental risks of toxic elements in surface sediments and they are widely used to evaluate the sediment quality (Smal et al 2015, Borowiak et al 2016. Potential Ecological Risk Index (RI) and Biological Risk Index based sediment quality guidelines (mERM-Q) are two of the most widely used sediment indices used to evaluate the environmental risks (Çiçek et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Many indices have been developed to evaluate the environmental risks of toxic elements in surface sediments and they are widely used to evaluate the sediment quality (Smal et al 2015, Borowiak et al 2016. Potential Ecological Risk Index (RI) and Biological Risk Index based sediment quality guidelines (mERM-Q) are two of the most widely used sediment indices used to evaluate the environmental risks (Çiçek et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In order to understand the spatial distribution of copper throughout the Guarapiranga ELU, a kriging interpolation method was implemented using Geovisual v. 5.0 software, following the procedure of Yamamoto and Landim (2015). This technique has been used in other similar studies (Smal, 2015;Batista, 2011;Alcantara, 2008;Burgos-León et al, 2012), and it has been shown to be an excellent tool for spatial analysis (Cressie, 1993;Camargo et al, 1999Camargo et al, , 2001Machado et al, 2004).…”
Section: Copper Spatial Interpolation and Spatial Analysismentioning
confidence: 99%
“…The chemical composition of bottom sediments, which are an integral part of aquatic environment, is conditioned by many natural and anthropogenic factors. It results from the geological structure of the catchment, land geomorphology, climate conditions, the way of management and use of catchment area, as well as the amount of contaminants reaching surface waters (Smal et al 2015). The natural sources of metals and metalloids in water bodies are atmospheric inputs, as well as geological weathering of rocks and soil (Ghaleno et al 2015;Wardhani et al 2017), but the majority of these toxic elements are of anthropogenic origin (mining, disposal of wastewaters, metal chelates from different industries, use of fertilizers, atmospheric deposition, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Within Kłodnica catchment, hard coal mines, industrial plants and wastewater treatment plants, etc., are located (Barbusińki and Nocoń 2011). It is important to note that properties of toxic elements, i.e., their concentrations, non-biodegradability and toxicity are the major reason for their monitoring in an aquatic environment (Smal et al 2015). Strong attention should be, therefore, put to ecological state of contaminated water bodies located in Silesian Region, which makes this issue one of the most current research topic in Poland.…”
Section: Introductionmentioning
confidence: 99%